The preferential treatment of green bonds - Francesco Giovanardi; Matthias Kaldorf; Lucas Radke; Florian Wicknig (Deutsche Bundesbank, 2022)
We study the preferential treatment of green bonds in the central bank collateral framework as an environmental policy instrument within a DSGE model with environmental and financial frictions. In the model, green and carbon-emitting conventional firms issue defaultable corporate bonds to banks that use them as collateral. The collateral premium associated to a relaxation in collateral policy induces firms to increase bond issuance, investment, leverage, and default risk. Collateral policy solves a trade-off between increasing collateral supply, adverse effects on firm risk-taking, and subsidizing green investment. Optimal collateral policy is characterized by modest preferential treatment, which increases the green investment share and reduces emissions. However, welfare gains fall well short of what can be achieved with optimal emission taxes. Moreover, due to elevated risk-taking of green firms, preferential treatment is a qualitatively imperfect substitute of Pigouvian taxation on emissions: if and only if the optimal emission tax can not be implemented, optimal collateral policy features preferential treatment of green bonds.
Keywords: E44; E58; E63; Q58; 330; Green Investment; Collateral Framework; Environmental Policy